Pengembangan Sistem Presensi Mahasiswa Berbasis RFID Menggunakan KTM di Universitas Pamulang - Nazwa Nur Farida; Amelia Sari; Zahrani Putri Solehah (Journal of Information Systems and Business Technology, 2025)
This study aims to develop and evaluate the effectiveness of a student attendance system based on Radio Frequency Identification (RFID) using Student Identity Cards (KTM) as an alternative to the manual attendance method commonly used at the Faculty of Informatics Engineering, University of Pamulang. The manual attendance process has several limitations, including slow processing time, potential fraud, data entry errors, and lack of integration with academic systems. This research employs a quantitative approach with a field experiment method involving 60 students and 3 lecturers as respondents. The developed RFID attendance system was tested based on speed, accuracy, and user perception. The results indicate that the RFID system significantly accelerates the attendance process from 20–25 seconds to only 2–3 seconds per student. The system also achieves an accuracy rate of 98.5%, effectively minimizing recording errors and eliminating attendance fraud.